Accelerating innovation and impact in EU-Africa collaboration for sustainable food systems - D'Alessandro, Cecilia; Menza, Gianpiero (2025)
This policy brief focuses on the critical importance of fostering the uptake and impact of research and innovation (R&I) in agrifood systems, particularly within the context of EU-Africa collaboration. As Africa faces mounting challenges from climate change, resource scarcity, and food insecurity, R&I should not only produce innovative solutions but also facilitate their widespread adoption and scaling. Achieving sustainable, inclusive, and resilient agrifood systems in Africa requires translating science and technological advances into practical, large-scale applications. The policy brief examines the EU-Africa R&I partnership, addressing key barriers to innovation uptake and exploring how to facilitate the scaling of agrifood innovations. It also draws on insights from other global initiatives and the broader innovation landscape, offering a comprehensive perspective on the challenges and opportunities in promoting the uptake of innovation.